Bacteriophage‐antibiotic combination therapy for multidrug‐resistant Pseudomonas aeruginosa: In vitro synergy testing - Holger, Dana J.; Lev, Katherine L.; Kebriaei, Razieh; Morrisette, Taylor; Shah, Rahi; Alexander, Jose; Lehman, Susan M.; Rybak, Michael J. (Journal of applied microbiology, 2022)
Aims Here, we investigate the impact of phage‐antibiotic combinations (PAC) on bacterial killing, resistance development and outer membrane vesicle (OMV) production in multidrug‐resistant (MDR) P. aeruginosa. Methods and Results After screening 10 well‐characterized MDR P. aeruginosa strains against three P. aeruginosa phages, representative strains, R10266 and R9316, were selected for synergy testing based on high phage sensitivity and substantial antibiotic resistance patterns, while phage EM was chosen based on host range. To understand the impact of phage‐antibiotic combinations (PAC) against MDR P. aeruginosa, time‐kill analyses, OMV quantification and phage/antibiotic resistance testing were performed. Phage and meropenem demonstrated synergistic activity against both MDR strains. Triple combination regimens, phage‐meropenem‐colistin and phage‐ciprofloxacin‐colistin, resulted in the greatest CFU reduction for strains R9316 (3.50 log10 CFU ml−1) and R10266 (4.50 log10 CFU ml−1) respectively. PAC resulted in regained and improved antibiotic susceptibility to ciprofloxacin (MIC 2 to 0.0625) and meropenem (MIC 32 to 16), respectively, in R9316. Phage resistance was prevented or reduced in the presence of several classes of antibiotics and OMV production was reduced in the presence of phage for both strains, which was associated with significantly improved bacterial eradication. Conclusions These findings support the potential of phage‐antibiotic synergy (PAS) to augment killing of MDR P. aeruginosa. Systematic in vitro and in vivo studies are needed to better understand phage interactions with antipseudomonal antibiotics, to define the role of OMV production in P. aeruginosa PAC therapy and to outline pharmacokinetic and pharmacodynamic parameters conducive to PAS. Significance and Impact of Study This study identifies novel bactericidal phage‐antibiotic combinations capable of thwarting resistance development in MDR and XDR P. aeruginosa strains. Furthermore, phage‐mediated OMV reduction is identified as a potential mechanism through which PAC potentiates bacterial killing.